Exploring the Pattern of Knowledge Management Practices in WhatsApp-Based Interactions among Indonesian EFL Learners - Ahysta Favviru Noor Illah; Movi Riana Rahmawanti; Linda (Universitas Islam Negeri Palopo, 2026)
Knowledge Management (KM) Practices play an essential role in supporting language learning, particularly in technology-mediated environments. Although previous studies have highlighted the importance of knowledge creation, sharing, utilization, and storing in educational context, limited research has investigated which KM dimensions are most prominent within WhatsApp-mediated EFL interactions. This study investigates the pattern of Knowledge Management practices in WhatsApp-based interactions among Indonesian university EFL students. An explanatory mixed-methods design was employed, involving a Likert-scale questionnaire administered to 33 students and semi-structured interviews with 15 participants. The findings indicate that knowledge storing (M = 3.47) and knowledge sharing (M = 3.38) were categorized as very high, suggesting that WhatsApp effectively supports knowledge storing and sharing processes. Knowledge creation (M = 3.12) was categorized as high, indicating that students were able to construct new understanding through collaborative discussion. In contrast, knowledge utilization (M = 2.85) received a comparatively lower score, suggesting challenges in applying acquired knowledge to learning tasks. Qualitative findings further revealed that WhatsApp promoted accessibility, flexibility, and active participation; however, structured instructional guidance remains necessary to facilitate deeper knowledge utilization. These findings contribute to Knowledge Management theory by demonstrating how mobile-mediated interactions support different KM dimensions in EFL contexts. Overall, WhatsApp-based interactions appear to be an effective platform for facilitating Knowledge Management practices, particularly knowledge storing and sharing among EFL learners.